НаноАрт та металургія: використання штучного інтелекту для обробки структур металів та сплавів - Воденнікова, О.С.; Воденніков, С.А. (Physico-technological Institute of Metals and Alloys, 2026)
The impact of artificial intelligence (AI) on the educational process is shown, in particular its capabilities and limitations for all participants in the educational process. The focus is on the use of artificial intelligence during distance learning as a virtual assistant for performing laboratory and practical classes in the specialty G10 “Metallurgy”. The emphasis is on the use of modern information technologies when working with metal and alloy structures as objects of research when creating NanoArt images. NanoArt as a symbiosis of science and art visualizes the invisible world of atoms and molecules, reflecting the laws of nature that are present at both the macro and micro levels. The paper compares the possibilities of using both artificial intelligence (for example, ChatGPT) and graphic editors (for example, Adobe Photoshop CS and Paint 3D) to create NanoArt images. The mechanism of transforming a black-and-white image of the structure of metals and alloys into multicolored pictures is shown, in which, thanks to their creative approach and sometimes “repainting” of some details of the image, the authors see completely new, and sometimes unexpected compositions – landscapes, animals, objects and other images. It is determined that artificial intelligence is an effective tool for optimizing the educational process and facilitates the work of both scientific and pedagogical workers and higher education students, creating broad opportunities for improving the quality of education. However, it cannot replace traditional learning, but is only an assistant capable of significantly enriching the organization of the educational process and improving the quality of educational services provided that it is used ethically and rationally.